Antarala (vestibule) of the temple - Temples of India Project Team (Jio Institute, 2024)
The antarala (vestibule) of the temple has four pillars. It is a rectangular plain passage that connects the mandapa (pillared hall) with the garbhagriha (sanctum sanctorum). This section of the temple structure dates to the Gupta period, as evident by a Gupta Brahmi inscription engraved on one of the pillars (on the right). The antarala leads to the garbhagriha which has a beautifully carved T-shaped door frame, one of the characteristics of Gupta-period temples. The doorframe of the garbhagriha has multiple shakhas, which are carved with figures of the river goddesses on each side at the bottom and dwarf figures and floral decorations above them. The antarala leads to the garbhagriha which has a beautifully carved T-shaped door frame, one of the characteristics of Gupta-period temples. The bottom of the shakha depicts river goddesses Ganga, on Makara, and Yamuna on Kachhappa, with their attendants. Above them, beautiful undulating creepers are shown. The shakha next to it shows standing dvarapalas, on each side, holding a weapon and flanked with dwarf figures performing different activities such as dancing, singing, and playing musical instruments.